Potentiometric and Blood Plasma Simulation Studies of Nickel(II) Complexes of Poly(amino)amido Pentadentate Ligands: Computer Aided Metal-Based Drug Design. (12th October 2014) - Odisitse, Sebusi; Jackson, Graham E.
Abstract : The thermodynamic equilibria of nickel(II) with N, N′-di(aminoethylene)-2, 6-pyridinedicarbonylamine (L1), Bis-(N, N-dimethylethyl)-2, 6-pyridinedicarboxamide (L2), and N, N′-bis[2(2-pyridyl)-methyl]pyridine-2, 6-dicarboxamide (L3) have been studied at 25°C and an ionic strength of 0.15 mol dm −3 by glass electrode potentiometry. The protonation and formation constants added to blood plasma model predict that Cu(II) competes effectively against Ni(II), Zn(II), and Ca(II) for these ligands in vivo .